Who Are the Poor in Rural and Coastal Sumatra? A Monetary and Multidimensional Inquiry - barika barika; Ririn Nopiah; Romi Gunawan; Iin Inayati; Aan Zuyanto (Integrated Journal of Business and Economics (IJBE), 2026)
This study analyses the determinants of poverty in rural and coastal areas using a microdata approach, which provides a more in-depth analysis of individual and household characteristics. This study using secondary data sourced from the Central Statistics Agency (BPS), which is microdata at the individual and household levels. The data consists of two sources, namely the National Socio-Economic Survey (SUSENAS) and the Village Potential (PODES) for the 2023 period. The unit of analysis used in this study is households with a population aged 15 years and above who are poor and live on the rural coast of the island of Sumatra. Analysis of the influence of household socio-economic characteristics on multidimensional poverty using the logistics multinomial regression method. This study found that social, economic, demographic, and infrastructure variables determine the level of household poverty in coastal Sumatra. It has been proven that education increases the likelihood of households escaping poverty while reducing its impact, both in monetary and multidimensional aspects. In addition, access to credit and Health Insurance (Askes) offers substantial social and economic capital that improves household well-being. Access to technology is also a key factor in improving the well-being of coastal communities, highlighting the value of digitalization in improving the economy of low-income households